Risks to REDD+: potential pitfalls for policy design and implementation - Loft, L.; Pham Thu Thuy; Wong, Grace Y.; Brockhaus, Maria; Le, D.N.; Tjajadi, J.S.; Luttrell, C. (Cambridge University Press, 2017)
International negotiations for reducing emissions from deforestation and forest degradation and the enhancement of forest carbon stocks (REDD+) under the UN Framework Convention on Climate Change (UNFCCC) were finally concluded in 2015. However, due to the complex design and implementation processes of REDD+ policies and measures, including benefit sharing at national and subnational levels, several challenges exist for sustainably reducing emissions while simultaneously managing the provision of social and environmental side-objectives. We review the realities of REDD+ implementation in 13 REDD+ candidate countries and the risks related to REDD+ policies and benefit sharing based upon a synthesis of the findings presented in ‘country profiles’ that were developed between 2009 and 2013 as part of the Center for International Forestry Research's (CIFOR) Global Comparative Study on REDD+. We find that REDD+ policies in all countries studied are at high risk of ineffectiveness, inequity and inefficiency. By classifying these risks and understanding not only their impacts on different stakeholder groups, but also the consequences for achieving specific objectives, countries can identify solutions in order to address these shortcomings in their implementation of REDD+.